KAJIAN WAKTU PEREBUSAN TERHADAP KARAKTERISTIK PAPAN SERAT TANDAN KOSONG KELAPA SAWIT DENGAN PEREKAT ASAM SITRAT - Agus Maulana; Prasetyo, Kurnia Wiji; Bachtiar, Gina (LPPM, Universitas Negeri Jakarta, 2020)
The This research aimed to obtain technical data on density, moisture content, thickness swelling, water absorption, modulus of rupture, modulus of elasticity, internal bonding, and screw withdrawal from EFB fiber whether eligible SNI 03-2105-2006. Material of fiberboard using waste of EFB fiber was 2 to 4 cm which 2 mesh in size sieve and retained on 10 mesh. Fiberboard to be created consisting of three types, namely without boiling, boiled for 2 hours, boiled for 4 hours with a grade adhesive 10 %, 20 %, and 30 %. The size of the board is 25 cm ᵡ 25 cm ᵡ 0.9 with 5 sample of test specimens. The research used experimental method. The study was conducted in the laboratory Biomaterials Indonesian Institute of Sciences (LIPI), located in Jalan Raya Bogor Km. 46, Cibinong. The execution time between June 2014 to October 2014. The results show value of physical test consisting of density, moisture content, water absorption and thickness swelling already qualified SNI 03-2105-2006. The best result show value found on fiberboard with boiling 4 hours with a grade adhesive 30%, wihch density value of 0.65 g / cm3, water content of 7.72 % , water absorption 64.45 %, thickness swelling 4.70 %, MOE 17.457 kgf/cm2, MOR 117.2 kgf/cm2, internal bonding of 3.12 kgf/cm2 and screw withdrawal 21.58 kgf. This values show the test mechanical properties of fiberboard from EFB with adhesive citric acid not qualify SNI 03-2105-2006. Keywords: EFB fiber, fiberboard, boiling